Cranial neuropathy and severe pain due to early disseminated Borrelia burgdorferi infection. (23rd January 2018) - Ebner, Derek; Smith, Kelsey; DeSimone, Daniel; Sohail, Muhammad Rizwan
Abstract : A 61-year-old man presented to the emergency department in the summer with a right seventh cranial nerve lower motor neuron palsy and worsening paraesthesias for 6 weeks. He had debilitating pain at the scalp and spine. Prior work up was unrevealing. The patient resided in the upper Midwest region of the USA and worked outdoors, optimising the landscape for white tailed deer. Repeat cerebrospinal fluid testing revealed a lymphocytic pleocytosis and positive IgM Lyme serology. Brain MRI demonstrated enhancement of multiple cranial nerves bilaterally. He was diagnosed with early Lyme neuroborreliosis and treated with 28 days of intravenous ceftriaxone. While the painful meningoradiculitis, also known as Bannwarth syndrome, is more commonly seen in Europe, facial palsy is more frequently encountered in the USA. Clinical manifestations of neuroborreliosis are important to recognise as the classic presentation varies by geography and on occasion repeat serological testing may be necessary.